RESEARCH OF THE VISION OF THE ROMAN CATHOLIC CHURCH IN SOVIET HISTORIOGRAPHY (Південний архів (історичні науки), 2022)
Purpose. The article examines the communist narratives of the Roman catholic church within the borders of the USSR in soviet literature and way so covering the catholic church, its clergy and laity in the historiography of the time and directly before society, analyzes the process of coverage of the Roman catholic church in the Soviet period. Methods. During the research the comparative-historical method, the historical-systematic method, the structuralthematic principle of historiography and the methods of analysis and synthesis of historical sources were used. Results. Based on the methods, the following results were achieved: analysis and research of historical sources of Soviet historiography in which the issue of religious processes of the Roman catholic church in the Soviet period within the territory of the former soviet union was revealed; the main provisions of the anti-religious propagandists of that time regarding the leveling of the structure of the church and its liquidation as a separate institution were established; the influence of state authorities, influencers of that time on the transformation of society in the attitude to the Roman catholic church in general and parishioners and laity in particular. An analysis of the literature widely disseminated and used by the then party elite identified the main provisions used to turn the laity away from the church, as well as the ideas used to create artificial conflicts within the country on religious grounds. Soviet historiography of the Roman catholic church and its clergy delivered extremely radical speeches and almost always did not cover them objectively, as it misinterpreted historical processes related to the church. One of the results of the study is the establishment of these inaccuracies. Conclusions. The policy of atheizing society, mass cruel punishments in the form of imprisonment, deportation to remote regions of the USSR and executions were intended to intimidate society and get rid of individuals who did not obey the regime. However, even such illegal actions did not yield the desired result, as the faith and its faithful continued their struggle for the right to exist in the totalitarian conditions of the Soviet Union.
Keywords: atheism, Soviet propaganda, Roman Catholics, priests, USSR.